Innovation, Bestsellers and Digitization - Where to Find the Needle in the Haystack? - Georg Goetz; Daniel Herold; Phil-Adrian Klotz; Jan Thomas Schaefer (Philipps-University Marburg, School of Business and Economics, 2020)
We empirically analyze the role of e-Commerce and brick-and-mortar retailers in discovering new bestsellers in the book market, using the German market as an example. Using an AR(1)-Process, we find that when a title becomes a bestseller sales increase in e-Commerce and decrease in brick-and-mortar stores relative to a title that is not on the bestseller-list. This finding implies that consumers in the online channel respond by increasing sales upon receiving a quality signal (i.e., a title becoming a bestseller). Consumers in the offline channel seem to already know that title so that, compared to a title that is not on the bestseller-lists, sales are decreasing. This might imply that consumers in the offline channel are more likely to read future bestsellers.
Keywords: 330; Buchhandel; Online-Handel; Absatz; Konsumentenverhalten; Produktqualität; Signalling; Deutschland